Plan de mejora continua en el proceso de revisión de contenedores vacíos para la Empresa CONTECARGA S.A. - Del Valle Loor, Ronald Leonel (2024)
This research work is based on the continuous improvement in the inspection of empty containers in the warehouses of shipping companies located in the cities of Guayaquil and Quito. In order to know the current situation, a survey was conducted to know the level of satisfaction and the factors that indicate a bad inspection and why the containers are rejected by the exporters. An interview was also conducted with a technical engineer in the container inspection process who is accredited by the SAE (Ecuadorian Accreditation Service). We planned to design a procedure based on the information obtained in the interview and reference with the IICL and BASC standard, where the most relevant points to be considered at the time the inspectors must perform the inspection are contemplated. In addition, a training schedule was proposed with relevant topics to the inspection of empty containers in order to increase the competences of the personnel.